Study of bacteria isolated from the foot pad of Spheniscus magellanicus with and without bumblefoot Estudo de bactérias isoladas de coxins plantares de Spheniscus magellanicus com e sem bumblefoot - L.G. Osório; M.O. Xavier; S.R.L. Ladeira; R.P. Silva Filho; R.O. Faria; G.D'Á. Vargas; A.L. Cabana; J.R.B. Mello; M.C.A. Meireles (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2013)
The bumblefoot or pododermatitis is among the diseases with the highest morbidity in Magellanic penguins, sometimes evolving to septicemia and death. Therefore, this study aimed to relate the main species involved in the disorder, as well as the in vitro susceptibility profile of the microorganisms against routine antimicrobial usage in Veterinary Medicine. During two years in vivo material was harvested from 200 footpads (n=100 animals) for microbiological analysis and in vitro susceptibility tests against the Antibiotic enrofloxacin, streptomycin, penicillin and cephalosporin. Bacteria have been identified both as part of permanent and transient microbiota, also being associated to 100% of the pododermatitis cases. The most prevalent genus were Staphylococcus and Corynebacterium. The antibiograms of all the isolated bacteria resulted in greater susceptibility of the strains facing cephalosporin, followed by enrofloxacin, streptomycin and penicillin. O bumblefoot ou pododermatite está entre as afecções de maior morbidade em pinguins-de-magalhães, podendo evoluir para septicemia e óbito. Portanto, o presente estudo objetivou relacionar as principais espécies bacterianas envolvidas na afecção, bem como o perfil de susceptibilidade in vitro destes microrganismos frente a antimicrobianos de uso rotineiro em medicina veterinária. Durante o período de dois anos, foi realizada colheita de material in vivo de 200 coxins plantares (n=100 animais) para análise microbiológica e testes de susceptibilidade in vitro frente aos antibióticos enrofloxacina, estreptomicina, penicilina e cefalosporina. Bactérias foram identificadas tanto como parte da microbiota permanente quanto da transitória, bem como estiveram associadas a 100% dos casos de pododermatite. Os gêneros mais prevalentes foram Staphylococcus e Corynebacterium. Os antibiogramas de todas as bactérias isoladas resultaram em maior sensibilidade das cepas frente à cefalosporina, seguida de enrofloxacina, estreptomicina e penicilina.